PENGEMBANGAN KEMAMPUAN FOTO PRODUK MAHASISWA POLITEKNIK NEGERI MEDIA KREATIF SEBAGAI MEDIA PEMASARAN PADA UMKM KACAMATA BRAND HALOPTIK - Syafriyandi, Syafriyandi; Syaputra, Dadang; Fitriady, Mochamad Yunus; Sudirman, Sudirman (Yayasan Education and Social Center, 2024)
The aim of this research is to develop students' product photo capabilities as marketing media for Haloptik Brand Glasses. The research applies qualitative descriptive data analysis methods. The data analysis used in this research refers to the Miles and Huberman Model, namely through the stages of data reduction, data presentation, and drawing conclusions. This research explains the data, conditions and facts found and provides solutions to problem solving using production-based student studies. The research subjects were of Haloptik Brand Glasses. Data is accumulated through performance instruments and student learning outcomes in completed assignments, designed work products, presenting work products and reporting results. The results obtained are in the form of photo content that is in accordance with the Digital Funneling Marketing concept and analyzed by applying qualitative descriptive techniques. The results of content analysis are used as marketing media for Optik Brand Haloptik